Comparison of Physical and Mechanical Properties of Bamboo Laminates With and Without Natural Fiber Reinforcement - Mochamad Chanan; Galit Gatut Prakosa; Aditya Galih Kurniawan (Jurnal Ilmu dan Teknologi Kayu Tropis, 2022)
Present study of engineered bamboo as an alternative to wood aims to determine the difference of physical-mechanical properties, as well as correlation of the observed properties consist of moisture content, density, modulus of elasticity (Eapp), and modulus of rupture (SR). Bambusa blumeana Schult. & Schult. F and Gigantochloa atroviolacea Widjaja, Agave sisalana Perrine, Hibiscus cannabinus L, and urea-formaldehyde resin as an adhesive used to produce natural-fibre-reinforced and non-reinforced laminated bamboo lumber (LBL). Specimen dimension accordance with ASTM standard D143-14. Test methods and equations accordance with ASTM standard D198-15. Statistical analysis includes analysis of variance, correlation, and regression. Result show properties of the interactions within AO, AK, AS, BO, BK, and BS ranged between 6,40% to 8,00% on MC, 0,62 g/cm3 to 0,74 g/cm3 on density, 12,71 GPa to 37, 70 GPa on MOE, and 62,64 MPa to 104,24 MPa on MOR respectively. Relationship between variables revealed linear negative correlation between MC versus density (R = –0,786), and MC versus MOR (R = –0,666). Linear positive correlation between density versus MOE (R = 0,508), density versus MOR (R = –0,578), and MOE versus MOR (R = –0,793).